Com a palavra, as crianças assentadas: as infâncias camponesas a partir da percepção dos seus sujeitos - Nascimento, Ana Clara da Silva (2023)
The assignment comes from the triangulation of three categories: Agricultural Childhood, Countryside Education and Popular Education. We chose as a main goal to understand the configurations of life in the countryside and agricultural childhoods from the perspective of children. The research was guided by the following specific objectives: Highlight the images that children have about childhood in the countryside; define the children's vision about the school and the community; identify the games, tasks that children experience in everyday life in the field and at school. Our research was methodologically based on the principles of Popular Countryside Education, seeking, as highlighted by Freire (1967), an active, dialogic and critical method. The assignment takes a qualitative approach, we carried out courses of action such as: art study, case study and a bibliographical research, based on authors such as: In the theoretical-methodological prism, this assignment was based on the approach of the Sociology of Childhood in Latin America, a scientific field which claims that children are capable of carrying out interactions and giving meaning to their actions, as social subjects, as active beings capable of building, of transforming, (re)inventing and recognizes that children are not universal, understanding that Latin American children have agendas and interests inherent in their realities. The subjects of our research are twenty (20) Agricultural Children, students of the multigrade class of the 3rd, 4th and 5th year of the initial years of fundamental education at the school of the Assentamento Chico Mendes I. The field of Popular Education in the Countryside is a territory with specificities and own and diversified ways of life, which will result in childhoods that keep different characteristics and ways of life, ways of thinking and living. The children express the social issues of the living spaces in which they are inserted, they make the countryside a place of presence and their routine is divided into tasks together with the family, the school, the church and the Movimento dos Trabalhadores Rurais Sem Terra. Their functions of studying, helping their parents and fulfilling obligations at the Assentamento are mediated by toys and games, and from this playfulness perspective, rural children produce agrarian capital and a culture in the farmer territory.